2000
DOI: 10.1007/s11920-000-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Treating schizophrenia earlier in life and the potential for prevention

Abstract: Early detection and intervention in schizophrenia has captured increasing attention of clinicians and clinical researchers in the past decade. It has obvious public health value for active first psychosis but it also holds potential for changing the course of disorder in ways that supercede symptom control. The research bearing upon the early phase of disorder, especially that presented recently at the March/April 2000 meeting of The International Early Psychosis Association in New York, is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This included numerous studies of first-episode schizophrenia demonstrating a correlation between a shorter duration of untreated psychosis (DUP) and better prognosis. These data have been reviewed extensively and will not be detailed here (McGlashan, 1996 a , 1999, 2000). The evidence is positive but equivocal insofar as several studies have not replicated this correlation.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…This included numerous studies of first-episode schizophrenia demonstrating a correlation between a shorter duration of untreated psychosis (DUP) and better prognosis. These data have been reviewed extensively and will not be detailed here (McGlashan, 1996 a , 1999, 2000). The evidence is positive but equivocal insofar as several studies have not replicated this correlation.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…However, recent studies use a combination of markers to define the group at increased risk. A prodromally symptomatic phase with attenuated symptoms is unsurprisingly proving to be highly predictive of psychosis (McGlashan, 2000), but earlier more inclusive detection is of potentially greater value.…”
Section: Discussionmentioning
confidence: 99%
“…However, even taking all these childhood risk factors together would yield large numbers of false positives and have low predictive validity (Erlenmeyer‐Kimling & Cornblatt, 1987), making them of little clinical relevance. A possible exception during the early premorbid phase is the presence of impaired attention (McGlashan, 2000). Cornblatt, Obuchowski, Roberts, Pollack, and Erlenmeyer‐Kimling (1999) reported that impaired attention is a stable vulnerability marker in children that may be causally related to social difficulties.…”
Section: Before the Prodromementioning
confidence: 99%
“…An effective case management system that provides services and supports to persons not in the acute stages of their illness has the potential for reducing recidivism, promoting hospital utilization, and increasing community tenure (e.g., Test & Stein, 1978;Test, 1979;Solomon, 1992), and it might have a salutary effect on the long-term outcomes of these conditions (e.g., McGlashan, 2000;Norman & Lewis, 2005). Although ACT is an EBP in the U.S., there is reason to believe that some form of this service would have beneficial effects for persons receiving services from K-e-H. Case management would provide each person either discharged from the K-e-H inpatient unit or attending the day program with a case manager.…”
Section: Future Directionmentioning
confidence: 99%